Tinjauan Hukum Islam Terhadap Praktik Penguasaan Hak Atas Barang Jaminan Pada Bank Syari'ah - Dani El Qori; Achmad Sya'bi (MASADIR: Jurnal Hukum Islam, 2026)
The practice of controlling collateral rights in Islamic banks, particularly through the rahn tasjily scheme at PT Bank Syariah Indonesia Tbk (BSI) KCP Gresik Kota Baru, is implemented by submitting asset ownership documents such as SHM, SHGB, and BPKB as financing collateral, while the physical assets remain controlled and utilized by the customer. Based on analytical descriptive field research through observation, interviews, and documentation at BSI GKB, a review of Islamic law based on four schools of thought (madzhab) shows diverse views regarding the legitimacy of such control. This practice is considered most compatible with the Maliki School because it recognizes the concept of qabdh hukmi or legal control over documents to protect the bank's rights as the murtahin. Conversely, the Hanafi School considers this control practice inappropriate because the bank's control is only administrative, while the Syafii and Hambali Schools consider it inappropriate because it requires qabdh haqiqi or actual physical control over the collateral. Although there are differences in perspective in classical fiqh, the implementation of control over collateral at BSI KCP Gresik Kota Baru is legally and formally declared valid and has complied with applicable national regulations, namely DSN-MUI Fatwa Number 68/DSN-MUI/III/2008.